The effect of stimulation assistance through booklet media on the development of preschool-aged children - Nurmila, Nurmila; Jasmiati, Jasmiati; Rosyta, Rosyta; Elizar, Elizar; Prihati, Nova Sumaini; Putri, Hendrika Wijaya Katrini; Irnawati, Irnawati (Institute of Computer Science (IOCS), 2025)
Suboptimal growth and development in children can have adverse effects on health. This study aimed to determine the effect of developmental stimulation assistance using booklet media on the development of preschool-aged children in the working area of Samudra Public Health Center. This research was a quasi-experimental study using a one-group pretest-posttest design. The sample consisted of 23 mothers with children aged 4–5 years, selected using accidental sampling. The research instruments included a questionnaire, the KPSP (Pre-Screening Developmental Questionnaire), and a booklet. Data were analyzed using the Wilcoxon test. The results showed that family assistance using booklet media had a significant effect on both child development (p = 0.000) and maternal knowledge (p = 0.000). The study concludes that developmental stimulation assistance through booklet media significantly affects both the developmental status of preschool-aged children and maternal knowledge.